Research progress on moxibustion for relieving chemotherapy-induced adverse drug reactions in cancer patients (艾灸缓解肿瘤化疗相关不良反应的研究进展) - YA Liu (严柳); GAO Yaqian (高雅倩) (中西医结合护理)
Adverse drug reactions have a direct impact on the treatment effect and quality of life of patients with malignant tumors. Research has found that moxibustion can effectively relieve the chemotherapy-induced adverse drug reactions. This article summarized the interventional mechanism of moxibustion and its clinical application for relieving chemotherapy-induced adverse drug reactions, in order to guide the clinical practice and improve the quality of life of cancer patients with chemotherapy. (肿瘤化疗相关不良反应严重影响患者的治疗和生活质量。艾灸可以缓解恶性肿瘤化疗相关不良反应, 减轻患者临床症状。本研究就艾灸疗法干预机制及其用于缓解肿瘤患者化疗相关不良反应的研究现状进行综述, 以期更好地指导临床实践, 提高化疗患者的生活质量。)